2022
DOI: 10.3389/fchem.2022.984268
|View full text |Cite
|
Sign up to set email alerts
|

Structure and functions of Aggregation-Induced Emission-Photosensitizers in anticancer and antimicrobial theranostics

Abstract: Photosensitizers with Aggregation-Induced Emission (AIE) can allow the efficient light-mediated generation of Reactive Oxygen Species (ROS) based on their complex molecular structure, while interacting with living cells. They achieve better tissue targeting and allow penetration of different wavelengths of Ultraviolet-Visible-Infrared irradiation. Not surprisingly, they are useful for fluorescence image-guided Photodynamic Therapy (PDT) against cancers of diverse origin. AIE-photosensitizers can also function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Recently, luminogens with aggregation-induced emission (AIEgens) features showed broad application prospects for theranostic applications as PSs ( Hu et al, 2018 ; Kang et al, 2019 ; Dai et al, 2020 ; Abrahamse et al, 2022 ). A delightful phenomenon could be observed that AIEgens exhibited excellent fluorescence and effective ROS creation during aggregation state while showing poor emission in the monomer state, which was resulting from the restriction of intramolecular motions (RIMs) ( Mei et al, 2015 ; Wang et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, luminogens with aggregation-induced emission (AIEgens) features showed broad application prospects for theranostic applications as PSs ( Hu et al, 2018 ; Kang et al, 2019 ; Dai et al, 2020 ; Abrahamse et al, 2022 ). A delightful phenomenon could be observed that AIEgens exhibited excellent fluorescence and effective ROS creation during aggregation state while showing poor emission in the monomer state, which was resulting from the restriction of intramolecular motions (RIMs) ( Mei et al, 2015 ; Wang et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…Delivering a precise dose of singlet oxygen to tumors, affording control, is a current objective in cancer therapy and photomedicine. The light used to excite the PS during the clinical procedure is usually supplied through a catheter containing optical fibers, which serve to generate the excited PS and cytotoxic 1 O 2 [ 42 ].…”
Section: Introductionmentioning
confidence: 99%